End-to-End Performance Evaluation for MIMO-OSTBC Adaptive Modulation Over Rayleigh Fading Channel - Al-Omary, Alauddin (International Journal of Engineering and Technology, 2018)
This paper presents end-to-end performance evaluation for adaptive Orthogonal Space-Time Block Codes (OSTBC) Multiple Input Multiple Output (MIMO) communication system over frequency selective Rayleigh fading channel. The system operates with one, two, three or four transmit or receive antennas to transmit and receive any frame. The system uses an adaptation algorithm that dynamically adjusts the used number of transmit and receive antennas based on the difference between the target and actual frame-error rates (FER) of the overall system. In this way, the performance of the system can be controlled adaptively. Alamouti and other adaptation algorithms are implemented in this system. The results show that FER improve significantly as the SNR increases and when the SNR is small, the adaptive algorithms successfully adjust the use of MIMO antenna to compensate the impairment caused by the faded and noisy channel.Â Â